Investigation of chatter prediction in end milling using morphological studies on aluminum alloy (Al6061). (April 2022) - Shaik, Jakeer H; Mutra, Rajasekhara R; Galal, Ahmed M; Tanneeru, Sinivasa R
Future machine tools have to be highly powerful systems to maintain the needed intellectual performance and stability. The machine tool systems such as Spindle/Tool-holder/Tool assembly are necessary to be optimized for their functionality or cutting performance to meet the productivity and accessibility requirements of the user. Prediction of the dynamic behavior at the spindle tool-tip is, therefore, an important criterion for assessing the machining stability of a machine tool at the design stage. In commercial practice, the machine tool system is extensively influenced by the dynamic rigidity of the spindle system. In this work, a realistic dynamic high-speed spindle/milling tool holder/tool system model is elaborated based on rotor dynamics predictions. Using the finite element modeling with the Timoshenko beam theory, the frequency response at the tool-tip has arrived initially. Further, the numerical model is validated with 3D ANSYS and experimental modal testing. The theoretical stability lobe diagram (SLD) depends on the stiffness and damping properties of the cutting tool and distinguishes the stable and unstable cutting conditions. The mechanism of chatter formation is investigated experimentally during the end milling of Aluminum alloy (Al6061) by two different techniques. Experimental cutting tests are conducted at different depths of cuts, the corresponding vibration signals and cutting samples are examined using the Scanning electronic microscope (SEM) and optical microscope. These studies provide a detailed investigation to predict the stable and unstable cutting zones at different machining conditions.